Aqueous-based electrospun P(NIPAAm-co-AAc)/RSF medicated fibrous mats for dual temperature- and pH-responsive drug controlled release. Issue 1 (2nd January 2020) - Li, Juan; Zhu, Jingxin; Jia, Lan; Ma, Yanlong; Wu, Haijuan
Abstract : This paper presents a green friendly method for preparing dual temperature- and pH-responsive electrospun P(NIPAAm- co -AAc)/RSF fibrous mats for drug release. Abstract : This paper presents a green method for fabricating dual temperature- and pH-responsive electrospun fibrous mats from an aqueous-based blend poly( N -isopropylacrylamide- co -acrylic acid) (P(NIPAAm- co -AAc)) and regenerated silk fibroin (RSF) by employing electrospinning technique. P(NIPAAm- co -AAc) was synthesized by free radical solution polymerization and its low critical solution temperature (LCST) was in the physiological range (38.8 °C). The P(NIPAAm- co -AAc)/RSF fibers were prepared by electrospinning technology in the presence of the crosslinking agents (EDC·HCl and NHS) with water as solvent. After in situ crosslinking and water-annealing process, the water-stable composite fibrous mats were obtained. Scanning electron microscopy (SEM) and Fourier transform infrared spectroscopy (FTIR) were used to analyze the crosslinking process. Temperature and pH dual stimuli-responsive swelling-shrinking behavior of the fibrous mats were observed when the temperature was below and above the LCST of the copolymer at different pHs. In addition, rhodamine B-loaded the fibrous mats also showed dual temperature and pH controlled release behavior, demonstrating the potential use of the fibrous mats for "smart" controlled drug delivery applications.